2006
DOI: 10.1098/rspb.2006.3575
|View full text |Cite
|
Sign up to set email alerts
|

Host heterogeneity dominates West Nile virus transmission

Abstract: Heterogeneity in host populations and communities can have large effects on the transmission and control of a pathogen. In extreme cases, a few individuals give rise to the majority of secondary infections, which have been termed super spreading events. Here, we show that transmission of West Nile virus (WNV) is dominated by extreme heterogeneity in the host community, resulting in highly inflated reproductive ratios. A single relatively uncommon avian species, American robin (Turdus migratorius), appeared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
568
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 462 publications
(590 citation statements)
references
References 51 publications
19
568
2
1
Order By: Relevance
“…S1), even if their long-term suitability to support infections was lower. Host competence, or the tendency of each host species to become infected and maintain infection, also varies among species (6,15,30). Previous work involving Ribeiroia has shown that total host community competence decreases in more diverse assemblages with the progressive addition of "poor-quality" hosts (15), consistent with results of our field and experimental studies.…”
Section: Discussionsupporting
confidence: 88%
“…S1), even if their long-term suitability to support infections was lower. Host competence, or the tendency of each host species to become infected and maintain infection, also varies among species (6,15,30). Previous work involving Ribeiroia has shown that total host community competence decreases in more diverse assemblages with the progressive addition of "poor-quality" hosts (15), consistent with results of our field and experimental studies.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, bloodfeeding patterns effectively set the encounter rate between vector-borne parasites and hosts. Mosquitoes, which are important vectors for a diversity of pathogens, are known to feed heterogeneously across hosts by using some species disproportionately, relative to their abundance [13][14][15]. This heterogeneity in mosquito-feeding patterns can strongly influence disease transmission dynamics [3,4,13,16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, American Robin WNV prevalence was highest in the Modoc bioregion (12%), but in the San Joaquin Valley region it was quite low (2%). Although the American Robin is likely important in the spread of WNV (Kilpatrick et al 2006;Hamer et al 2009), fewer dead American Robins are reported or discovered by the California public compared to corvids, House Finches, and House Sparrows. In southern California, the House Finch and House Sparrow serve as reservoir populations for WNV because these two peridomestic species are frequent blood meal hosts for several Culex vectors (Thiemann et al 2012) and have been implicated in WNV amplification in that area (Molaei et al 2010).…”
Section: Bird Speciesmentioning
confidence: 99%
“…American Robins (Turdus migratorius) develop relatively high viremias when infected (Vandalen et al 2013), but do not suffer the high mortality common to corvids. They are a preferential host of Culex pipiens complex mosquitoes (Hamer et al 2009), and WNV spread in northeast and northcentral US has been attributed to American Robins (Kilpatrick et al 2006;Hamer et al 2009). Peridomestic House Finches (Haemorhous mexicanus) and House Sparrows (Passer domesticus) serve as reservoir and amplifying hosts in California Wheeler et al 2009;Molaei et al 2010) and have been associated with human WNV disease outbreaks (Kwan et al 2012), especially in the western US.…”
Section: Introductionmentioning
confidence: 99%